Electrolyte for NCM811 / graphite lithium ion battery, battery and battery preparation method

By using a new electrolyte in NCM811/graphite lithium-ion batteries, a dense interface film is formed by using the redox reaction of LiNO3, the problem of poor interface stability between the positive electrode and the negative electrode of NCM811 is solved, and the cycle stability and energy density of the battery are significantly improved.

CN119812488APending Publication Date: 2025-04-11YANTAI LIHUA ELECTRIC POWER TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510051563.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The interface stability of NCM811 positive electrode material and graphite negative electrode material in lithium-ion batteries is poor, resulting in battery cycle stability and safety issues.

Method used

A new electrolyte, including 3-methyl-2-oxazolidinone, methyl ethyl carbonate and diethyl carbonate, LiPF6 and LiNO3, is used to form a dense CEI film at the NCM811 interface through the redox reaction of LiNO3, and optimize the interface performance.

Benefits of technology

It significantly improves the interface stability of the NCM811 positive electrode and graphite negative electrode, extends the cycle life of the battery, reduces harmful side reactions, and improves the energy density and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812488A_ABST
    Figure CN119812488A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of methods or devices for directly converting chemical energy into electric energy, in particular to an electrolyte for an NCM811 / graphite lithium ion battery, the battery and a battery preparation method. The invention provides an electrolyte for an NCM811 / graphite lithium ion battery. The electrolyte is prepared from 3-methyl-2-oxazolidinone, methyl ethyl carbonate, diethyl carbonate, LiPF6 and LiNO3. The invention provides a lithium ion soft package battery which comprises electrolyte, a positive electrode material NCM811 and a negative electrode material graphite. The invention provides a preparation method of an NCM811 / graphite lithium ion soft package battery. The preparation method comprises the steps of electrolyte preparation, liquid injection of the soft package battery, high-temperature infiltration, formation and secondary final sealing. According to the invention, the interfacial properties of the NCM811 positive electrode and the graphite negative electrode are optimized, and the cycling stability and safety are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of methods or devices for directly converting chemical energy into electrical energy, and in particular to an electrolyte, a battery and a method for preparing the battery for an NCM811 / graphite lithium-ion battery. Background Art

[0002] With the rapid expansion of the portable electronic device market, the demand for battery technology is increasing, especially the demand for higher energy density and longer battery life. In this context, ternary lithium-ion batteries (LIBs) have become a popular candidate for the next generation of high energy density rechargeable batteries due to their excellent high energy density and high power output characteristics. In particular, when using high voltage and high capacity cathode materials such as NCM811, the energy density of LIBs is expected to exceed 300 Wh·kg -1 It will break the bottleneck of the power supply chain and bring disruptive changes to electric vehicles, portable devices and other fields.

[0003] However, the challenges faced by NCM811 positive electrode materials in practical applications are equally significant. The instability of its electrochemical performance is mainly due to the complexity and defects of the interface properties between the electrode and the electrolyte. While NCM811 with a high nickel ratio gives the battery a high energy density, it is also prone to complex reconstruction of the electrode surface during the charge and discharge process due to the high activity and chemical instability of nickel ions. This not only involves profound changes in the structure of the active material, but also triggers a series of negative interfacial reactions, such as the formation of the interface layer, increased contact resistance, and electrolyte decomposition, which seriously hinders the reaction kinetics rate and cycle stability of the battery. As a commonly used negative electrode material in LIBs, the performance stability and interface optimization of graphite are also crucial to the overall performance of the battery. When the electrolyte properties are poor, the interface performance between the graphite electrode and the electrolyte often cannot meet the requirements, resulting in uneven deposition and stripping of lithium ions on the graphite surface, which is easy to form lithium dendrites, and then cause internal short circuits and safety hazards in the battery. In addition, poor electrolytes will accelerate the wear and aging of graphite electrodes, resulting in rapid attenuation of battery capacity and shortened cycle life. More seriously, these interface performance defects may trigger harmful side reactions, such as continuous decomposition of the electrolyte and gas generation, which further consume the active lithium source and increase the internal pressure of the battery, posing a serious threat to battery safety and stability.

[0004] To address these challenges, researchers have conducted extensive and in-depth research and explored a series of modification measures aimed at enhancing the interfacial stability of NCM811 and optimizing the performance of graphite anodes, including but not limited to the following aspects: 1. Optimize the crystal structure of NCM811 cathode material: Single crystal NCM811: The single crystal structure is prepared by precisely controlling the synthesis conditions, reducing the barrier of lithium ion transmission, improving the cycle stability and rate performance. However, the preparation process is complex, the cost is high, and the mechanical strength is low, and it is easy to break or pulverize under external force.

[0005] Polycrystalline NCM811: Optimize the synthesis process, provide more lithium ion transmission channels, and alleviate volume expansion. However, interfacial reactions are prone to occur at the grain boundaries, resulting in loss of active materials and performance degradation; uneven grain size may also affect lithium ion transmission efficiency and rate performance.

[0006] 2. Improve the surface properties of NCM811 cathode material: Surface coating treatment: reduce direct contact with the electrolyte, reduce interface reaction, protect active substances, and improve cycle stability. However, it may increase material thickness and reduce lithium ion transmission efficiency; the uniformity and stability of the coating layer must be strictly controlled.

[0007] Bulk doping modification: Improve crystal structure and electrochemical properties, increase lithium ion mobility and electronic conductivity, and inhibit harmful phase changes and interface reactions. However, impurities or defects may be introduced, affecting crystal integrity and electrochemical activity; the type and concentration of doping elements need to be optimized and balanced.

[0008] 3. Optimize the interface performance of graphite anode: Surface modification: Chemical or physical modification of the graphite negative electrode surface, such as oxidation, fluorination, etc., to improve its wettability and interfacial stability with the electrolyte and reduce the formation of lithium dendrites. However, the modification process may increase costs, and it is necessary to ensure good bonding between the modified layer and the graphite matrix.

[0009] Electrolyte additives: Add specific additives such as fluoride and carbonate to the electrolyte to improve the interface performance between the graphite anode and the electrolyte and promote the uniform deposition and stripping of lithium ions on the graphite surface. However, the selection and concentration of additives need to be carefully optimized to avoid negative effects on other battery properties.

[0010] Solid electrolyte interface (SEI) optimization: By adjusting the electrolyte composition and charge and discharge conditions, a stable and uniform SEI film is formed on the surface of the graphite negative electrode to reduce the formation of lithium dendrites and the decomposition of the electrolyte. However, the formation and stability of the SEI film are affected by many factors, and its formation mechanism and optimization strategy need to be studied in depth.

[0011] Although researchers have tried a variety of modification measures, these methods all have limitations. Therefore, it is urgent to develop new, efficient and cost-controlled modification methods to solve the interface stability problem of NCM811 and optimize the performance of graphite anodes, and promote the development of high energy density lithium-ion battery technology. Summary of the invention

[0012] In view of the technical problem of poor interface stability of NCM811 / graphite lithium-ion batteries in the prior art, the present invention provides an electrolyte, a battery and a battery preparation method for NCM811 / graphite lithium-ion batteries, which optimize the interface properties of the NCM811 positive electrode and the graphite negative electrode, and improve the cycle stability and safety.

[0013] The invention provides an electrolyte for NCM811 / graphite lithium ion battery. The electrolyte comprises 3-methyl-2-oxazolidinone, ethyl methyl carbonate and diethyl carbonate, LiPF6 and LiNO3.

[0014] Furthermore, the volume ratio of 3-methyl-2-oxazolidinone, ethyl methyl carbonate and diethyl carbonate is 1:1:1.

[0015] Furthermore, the concentration of LiPF6 is 0.2 mol·L -1 , the concentration of LiNO3 is 1.0 mol·L -1 .

[0016] The invention provides a lithium ion soft-pack battery, wherein the positive electrode material is NCM811, the negative electrode material is graphite, and the electrolyte comprises 3-methyl-2-oxazolidinone, ethyl methyl carbonate and diethyl carbonate, LiPF6 and LiNO3.

[0017] The present invention provides a lithium ion soft pack battery, wherein the positive electrode material is NCM811, the negative electrode material is graphite, and the electrolyte comprises 3-methyl-2-oxazolidinone, ethyl methyl carbonate and diethyl carbonate (vol% 1:1:1), LiPF6 and LiNO3.

[0018] The present invention provides a lithium ion soft pack battery, wherein the positive electrode material is NCM811, the negative electrode material is graphite, and the electrolyte comprises 3-methyl-2-oxazolidinone, ethyl methyl carbonate and diethyl carbonate (vol% 1:1:1), 0.2 mol·L -1 LiPF6 and 1.0 mol·L -1 LiNO3.

[0019] The present invention provides a method for preparing a NCM811 / graphite lithium ion soft pack battery, comprising the following steps: S1, electrolyte preparation: prepare a mixed solvent of 3-methyl-2-oxazolidinone / ethyl methyl carbonate / diethyl carbonate (vol% 1:1:1), add LiNO3 and LiPF6 to the mixed solvent of 3-methyl-2-oxazolidinone / ethyl methyl carbonate / diethyl carbonate (vol% 1:1:1) at 25°C to make the concentration of LiNO3 be 1.0 mol·L -1 , the concentration of LiPF6 is 0.2 mol·L -1, prepare the electrolyte; S2, soft-pack battery injection: add electrolyte to the finished soft-pack battery with a capacity of 5Ah, and the injection coefficient is 3.5g / Ah; S3, high-temperature infiltration: place the soft-pack battery after injection at 45℃ for 24h to ensure that the electrolyte fully infiltrates the battery cell; S4, formation: place the battery at 25℃ for formation, and the formation step is to charge the battery to 4.2V with a constant current of 0.05C; S5, secondary final sealing: release the gas in the soft-pack battery after formation, and perform secondary packaging on the side.

[0020] The beneficial effects of the present invention are: The present invention uses a new type of high-polarity solvent to increase the solubility of LiNO3, forms a dense and strong CEI film at the NCM811 interface through the redox reaction of LiNO3, and stabilizes the electrode electrolyte interface. This method not only optimizes the interface properties of the NCM811 positive electrode, but also promotes the uniform transmission of lithium ions, reduces contact resistance, improves the reaction kinetics rate, inhibits electrolyte decomposition, reduces harmful side reactions, and prolongs battery life. At the same time, for the graphite negative electrode, the increase in LiNO3 solubility also promotes the uniform deposition and stripping of lithium ions on the graphite surface, reduces lithium dendrite formation, improves cycle stability and safety, enhances the wettability between graphite and electrolyte, improves charge transfer performance, and improves the charge and discharge efficiency and energy density of the battery. Therefore, the method of increasing the solubility of LiNO3 using a new type of high-polarity solvent, utilizing the redox reaction of LiNO3, and optimizing the electrochemical properties of the interface between NCM811 and the graphite electrode electrolyte at the same time provides strong support for the development of high-performance and high-energy-density LIBs.

[0021] The present invention increases the use of LiNO3 and reduces the use of LiPF6. The price of LiNO3 is much lower than that of LiPF6. By optimizing the production process and large-scale production, the production cost can be further reduced and the economic benefit can be improved.

[0022] The capacity decay rate of the lithium-ion battery of the present invention is significantly slowed down during the charge and discharge cycle, and the cycle stability is significantly improved. In particular, under high-rate charge and discharge conditions, the capacity retention rate of the battery is still maintained at a high level. The present invention effectively reduces the polarization phenomenon of the battery, improves the transmission efficiency of lithium ions, and significantly improves the charge and discharge efficiency of the battery.

[0023] The optimization of the interface film and the improvement of lithium ion transmission efficiency of the present invention significantly improve the energy density of the lithium ion battery of the present invention. The cycle life test shows that after hundreds of charge and discharge cycles, the lithium ion battery using the method of the present invention can still maintain a high capacity and performance stability, and the cycle life is significantly extended.

[0024] The lithium-ion battery of the present invention is applied to portable electronic devices, electric vehicles, energy storage systems and other fields, and has excellent performance and stability. In particular, in the field of electric vehicles, the battery can meet the requirements of long battery life, high safety and high energy density, providing strong support for the popularization and development of electric vehicles. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 The scanning electron microscope (SEM) images of the interface between the NCM811 positive electrode and the graphite (Gr) negative electrode after 200 cycles, wherein (a) corresponds to the corresponding proportional NCM811 positive electrode, (b) corresponds to the corresponding proportional graphite negative electrode, (c) corresponds to the example NCM811 positive electrode, and (d) corresponds to the example graphite negative electrode; Figure 2 Transmission electron microscope (TEM) images of NCM811 interface CEI films of the embodiment and comparative example, wherein (a) is the comparative example and (b) is the embodiment; Figure 3 The XPS spectra of the interfacial film components formed on the surface of NCM811 particles in the examples and comparative examples, wherein (a) is the comparative example and (b) is the example; Figure 4 It is the rate performance diagram of NCM811 / Gr soft pack battery after formation in the embodiment and the comparative example; Figure 5 It is the cycle performance diagram of NCM811 / Gr soft pack battery after formation of the embodiment and the comparative example. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0028] The present invention provides an embodiment as follows: B1 electrolyte preparation: Prepare 100 mL of MOX / EMC / DEC (vol% 1:1:1) mixed solvent, and weigh 6.9 g LiNO3 (1.0 mol·L-1 ) and LiPF63.04g (0.2 mol·L -1 ), 6.9 g LiNO3 and 3.04 g LiPF6 were added to the MOX / EMC / DEC (vol% 1:1:1) mixed solvent at 25°C to prepare the B1 electrolyte.

[0029] Soft-pack battery filling: Add B1 electrolyte to the finished soft-pack battery with a capacity of 5Ah, and the filling coefficient is 3.5g / Ah.

[0030] High temperature soaking: Place the soft-pack battery at 45°C for 24 hours after the injection to ensure that the electrolyte fully soaks the battery cell.

[0031] Formation: The battery is placed at 25°C for formation. The formation step is to charge the battery to 4.2V using a constant current of 0.05C.

[0032] Secondary final sealing: Release the gas in the soft-pack battery after formation and perform secondary sealing on the side.

[0033] Aging: The soft-pack battery is placed at 45°C for 48 hours for high temperature aging.

[0034] Cycle test: The soft-pack battery using B1 electrolyte was placed at 25°C for a long cycle test with a cycle current of 0.5C.

[0035] The present invention provides a comparative example as follows: B2 electrolyte preparation: Prepare 100 mL of EC / EMC / DEC (vol% 1:1:1) mixed solvent, and weigh 1.38 g of LiNO3 (0.2 mol·L -1 ) and LiPF615.2g (1.0 mol·L -1 ), 1.38gLiNO3 and 15.2gLiPF6 were added into EC / EMC / DEC (vol% 1:1:1) mixed solvent at 25°C to prepare B2 electrolyte.

[0036] Liquid injection for soft-pack batteries: Add B2 electrolyte to the finished soft-pack batteries with a capacity of 5Ah, and the injection coefficient is 3.5g / Ah.

[0037] High temperature soaking: Place the soft-pack battery at 45°C for 24 hours after the injection to ensure that the electrolyte fully soaks the battery cell.

[0038] Formation: The battery is placed at 25°C for formation. The formation step is to charge the battery to 4.2V using a constant current of 0.05C.

[0039] Secondary final sealing: Release the gas in the soft-pack battery after formation and perform secondary sealing on the side.

[0040] Aging: The soft-pack battery is placed at 45°C for 48 hours for high temperature aging.

[0041] Cycle test: The soft-pack battery using B2 electrolyte was placed at 25°C for a long cycle test with a cycle current of 0.5C.

[0042] The positive electrode material of the soft-pack battery in the embodiment and the comparative example is NCM811, which is a nickel-cobalt-manganese ternary positive electrode material, and the negative electrode material is graphite (Gr). The electrolyte in the embodiment and the comparative example, EC is ethylene carbonate, MOX is 3-methyl-2-oxazolidinone, EMC is ethyl methyl carbonate, and DEC is diethyl carbonate.

[0043] like Figure 1 (a) Figure 1 As shown in (b), after the NCM811 / Gr soft-pack battery using B2 electrolyte underwent 200 charge and discharge cycles, it was observed that the NCM811 active material particles were significantly broken. This phenomenon reveals that the CEI film formed on the surface of the NCM811 material during the formation stage is not dense enough, and it fails to effectively meet the performance standards and cannot completely block the direct contact between the NCM811 particles and the electrolyte. Therefore, in the subsequent cycles, continuous side reactions continue to occur, eventually causing the particles to break. In addition, the SEI film on the surface of the graphite negative electrode is not only abnormally weak, but also extremely unevenly distributed. Such an interface film is also difficult to meet the needs of the negative electrode in subsequent cycles, resulting in large-scale lithium deposition on the graphite surface, which accelerates the performance degradation and rapid deactivation of the battery. In contrast, Figure 1 (c) Figure 1 As shown in (d), the NCM811 / Gr soft-pack battery using electrolyte B1 shows significant advantages. The B1 electrolyte effectively enhances the compactness and uniformity of the CEI membrane and the SEI membrane, thereby forming a more solid protective barrier on the surface of the NCM811 positive electrode and the graphite negative electrode. This not only greatly reduces the direct contact between the electrolyte and the active material, effectively inhibits the occurrence of side reactions, but also significantly improves the cycle stability of the battery. Especially under high-rate charge and discharge conditions, the B1 electrolyte exhibits excellent ability to inhibit lithium precipitation, effectively avoiding the problem of lithium deposition on the surface of the graphite negative electrode and extending the service life of the battery. In addition, the B1 electrolyte also optimizes the ion conductivity of the electrolyte, improves the power density and energy efficiency of the battery, and provides a more reliable and efficient energy solution for electric vehicles and energy storage systems.

[0044] There is a significant difference in thickness between the CEI film formed on the surface of the NCM811 cathode using the B2 electrolyte and the B1 electrolyte, which has an important impact on the battery performance. Figure 2 As shown in (a), in the B2 electrolyte system, the CEI film formed on the surface of NCM811 is relatively thin, about 5 nm. Although this film can block the direct contact between the active ingredients in the electrolyte and NCM811 to a certain extent, due to its insufficient thickness, it may not be able to effectively withstand the mechanical stress and chemical corrosion generated during the battery charging and discharging process. In addition, the thinner CEI film may contain more defects and pores, allowing harmful components in the electrolyte to more easily penetrate into the interior of the NCM811 particles, triggering continuous side reactions and accelerating the decline of battery performance. In contrast, Figure 2 As shown in (b), in the system using the B1 electrolyte, the CEI film formed on the surface of NCM811 is significantly thickened, reaching about 18nm. This thicker CEI film not only provides a more solid and stable protective barrier, effectively blocks the direct contact between the active ingredients in the electrolyte and NCM811, reduces the occurrence of side reactions, but also can better withstand the mechanical stress and chemical corrosion generated during the battery charging and discharging process. In addition, the thicker CEI film may also have better ion conductivity, which helps to improve the power density and energy efficiency of the battery. In summary, the B1 electrolyte provides more reliable and efficient protection for the NCM811 positive electrode by forming a thicker CEI film, significantly improving the overall performance of the lithium-ion battery.

[0045] From the XPS spectrum, we can see that Figure 3 As shown in (a), the CEI film formed on the NCM811 interface using B2 electrolyte contains a small amount of inorganic components. Figure 3 As shown in (b), the interfacial film formed using the B1 electrolyte is rich in inorganic components. The formation of these inorganic components is attributed to the oxidation / reduction reaction of LiNO3, which produces highly conductive substances and forms inorganic substances such as LiNxOy and Li3N. The presence of these inorganic substances greatly promotes the Li + diffusion, thereby accelerating the charge transfer process.

[0046] like Figure 4 As shown, the battery using B1 electrolyte has better rate performance, which is due to the use of a large amount of LiNO3, which makes the interface film formed on the surface of NCM811 and Gr contain a large amount of inorganic components, making the lithium ion transmission performance of the interface film better.

[0047] like Figure 5As shown in the figure, the NCM811 / Gr soft-pack battery using the B1 electrolyte exhibits better cycle stability and longer battery life than the B2 electrolyte formula. This excellent performance is mainly due to the significant improvement in its interface properties. Specifically, the B1 electrolyte causes the NCM811 positive electrode and the graphite negative electrode surface to form a smoother and denser interface layer. This interface layer not only reduces the direct contact area between the active material and the electrolyte, but also effectively inhibits the occurrence of side reactions, thereby ensuring the stability of the battery during the charge and discharge cycle. In addition, the interface layer formed by the B1 electrolyte is thicker and rich in inorganic components than that of traditional electrolytes (such as the hypothetical comparative example B2 electrolyte). This thicker and inorganically rich interface layer provides a stronger protective barrier for the battery, allowing the battery to better withstand the mechanical stress and chemical erosion generated during the charge and discharge process. This not only further improves the cycle stability of the battery, but also significantly extends the life of the battery.

[0048] Although the present invention has been described in detail with reference to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art may easily think of changes or substitutions within the technical scope disclosed by the present invention, and these shall be within the scope of protection of the present invention.

Claims

1. An electrolyte for NCM811 / graphite lithium-ion battery, characterized in that: The electrolyte includes 3-methyl-2-oxazolidinone, ethyl methyl carbonate and diethyl carbonate, LiPF6 and LiNO3.

2. An electrolyte for NCM811 / graphite lithium-ion battery according to claim 1, characterized in that: The volume ratio of 3-methyl-2-oxazolidinone, ethyl methyl carbonate and diethyl carbonate is 1:1:

1.

3. An electrolyte for NCM811 / graphite lithium-ion battery according to claim 2, characterized in that: The concentration of LiPF6 is 0.2 mol·L -1 , the concentration of LiNO3 is 1.0 mol·L -1 .

4. A lithium-ion soft pack battery, characterized in that: Comprising the electrolyte as described in any one of claims 1 to 3, the positive electrode material of the lithium-ion soft-pack battery is NCM811, and the negative electrode material is graphite.

5. A method for preparing a NCM811 / graphite lithium-ion soft-pack battery, characterized in that: The following steps are involved: S1, electrolyte preparation: prepare a mixed solvent of 3-methyl-2-oxazolidinone / ethyl methyl carbonate / diethyl carbonate (vol% 1:1:1), add LiNO3 and LiPF6 to the mixed solvent of 3-methyl-2-oxazolidinone / ethyl methyl carbonate / diethyl carbonate (vol% 1:1:1) at 25°C to make the concentration of LiNO3 be 1.0 mol·L -1 , the concentration of LiPF6 is 0.2 mol·L -1 , prepare the electrolyte; S2, soft pack battery injection: adding electrolyte to the finished soft pack battery with a capacity of 5Ah, and the injection coefficient is 3.5g / Ah; S3, high temperature soaking: place the soft pack battery at 45°C for 24 hours after the injection to ensure that the electrolyte fully soaks the battery cell; S4, formation: the battery is placed at 25°C for formation, and the formation step is to charge the battery to 4.2V using a constant current of 0.05C; S5, secondary final sealing: release the gas in the soft-pack battery after formation and perform secondary sealing on the side.